A systematic review of hypervirulent Klebsiella pneumoniae research: bibliometric and topic modeling perspectives - Tian, Tian; Han, Hui; Guan, Zhi-Hui; Zhang, Ke; Huang, Xinghe; Wang, Wenyue; Zhang, Xuan; Zhang, Fei; Wei, Leijia; Zhang, Xin; Wang, Jia-He (Frontiers in Medicine, 2025)
Background/objectiveHypervirulent Klebsiella pneumoniae (hvKP) is an emerging global health threat, exhibiting increased virulence and multidrug resistance compared to classic K. pneumoniae. Understanding the research landscape surrounding hvKP is crucial for developing effective control strategies. This study aimed to comprehensively analyze the global research trends in hvKP from 2013 to 2024 using bibliometric and topic modeling techniques.MethodsData from 1,014 articles on hvKP, retrieved from the Web of Science Core Collection, were analyzed using Bibliometrix, CiteSpace, and VOSviewer to assess publication trends, collaborations, geographical distribution, and keyword co-occurrence. Latent Dirichlet Allocation (LDA) topic modeling was employed to identify key research themes.ResultsThe analysis revealed a steadily increasing volume of hvKP research, with China and the United States as major contributors. Four primary research themes emerged: high virulence phenotypes and mechanisms; drug resistance and treatment strategies; genetic and molecular mechanisms; and epidemiological and transmission characteristics. Research hotspots included virulence mechanisms, drug resistance, genomic detection approaches, and epidemiological features.ConclusionThis bibliometric analysis provides a comprehensive overview of hvKP research, highlighting key trends and research gaps. The identified research hotspots inform future research directions and contribute to the development of effective strategies for combating hvKP infections. The increasing research volume underscores the urgent need for continued investigation into this significant public health threat.